Pelatihan Digital Marketing Sebagai Upaya Peningkatan Pengetahuan Dan Keterampilan Guru Di SMP PGRI 3 Baturaja - Suryanto Suryanto; Haris Saputro; Defi Pujianto; Kadarsih Kadarsih; Didik Arifin; Rusidi Rusidi; Ari Sulfani (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
In the current era of digitalisation, digital marketing skills are crucial across various fields, especially in education. Teachers need to have knowledge and skills in digital marketing to support the promotion and branding of schools. SMP PGRI 3 Baturaja, a private school, faces competition in attracting new students by leveraging digital technology to showcase the school's activities and achievements. The purpose of this training is to enhance the knowledge of SMP PGRI 3 Baturaja teachers about the concepts and strategies of digital marketing and to develop practical skills in using various digital marketing tools and platforms. With this knowledge, it is expected that teachers can effectively improve the promotion and reputation of the school. The training is conducted through interactive and practical workshop sessions, including theoretical presentations, discussions, and hands-on practice. Participants will be provided with material on the basics of digital marketing, content strategies, and the use of social media. Additionally, there will be mentoring sessions for hands-on practice. After attending this training, based on the results of the questionnaires distributed to the participants, 86.7% of participants gained new knowledge about digital marketing, 85.7% acquired skills in copywriting with AI, and 80% gained skills in creating digital marketing content. The training participants were able to implement activities during digital marketing practice. SMP PGRI 3 Baturaja teachers are now more skilled in using various digital platforms to promote school activities and promotions on social media after the training.